PENGARUH FINANCIAL TECHNOLOGY DAN FINANCIAL LITERACY TERHADAP MINAT INVESTASI MAHASISWA UNIVERSITAS TEKNOLOGI DIGITAL - Dian Anita; Ayu Oktaviani (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Growing interest in investing, particularly among students, is influencediby the advancement ofifinancial technology andia high degree ofifinancial knowledge. Using a case study of students at the Digital Technology University, this studyiattempts to examine howIfinancial technologyiand financial literacy affectistudents' interest in investing. Students who have heard of or used fintech services are given questionnaires as part of this study's quantitative descriptive methodology. The Slovin formula is utilized to determine the number of respondents. To ascertainithe impactiof each independent variable (financialitechnology and financial literacy) on the dependent variable (investment interest), theicollected dataiwere subjected to multiple lineariregression analysis. Theistudy's findings demonstrate thatistudents' interest in investing is positivelyiand significantlyiimpacted by financial technology, with theisimplicity of use and innovation of digital financial services boosting students' motivation to make investments. Furthermore, a greater comprehension of the advantages and disadvantages of investing is facilitated by a higher degree of financial literacy, which in turn promotes more logical investment choices. Meningkatnya minat berinvestasi, khususnya di kalangan mahasiswa, dipengaruhi oleh kemajuan teknologi finansial dan tingginya tingkat pengetahuan finansial. Dengan menggunakan studi kasus mahasiswa di Universitas Teknologi Digital, penelitian ini berupaya untuk meneliti bagaimana teknologi finansial daniliterasi keuangan memengaruhi minatimahasiswa untukiberinvestasi. Mahasiswa yang pernah mendengar atau menggunakan layanan fintech diberikan kuesioner sebagai bagian dari metodologi deskriptif kuantitatif penelitian ini. Rumus Slovin digunakan untuk menentukan jumlah responden. Untuk memastikan dampak dari setiap variabel independen (teknologi finansial dan literasiikeuangan) terhadap variabel dependen (minatiinvestasi), data yangiterkumpul dikenakan analisis regresiilinear berganda. Temuanipenelitian menunjukkanibahwa minatimahasiswa untukiberinvestasi dipengaruhi secara positif dan signifikan oleh teknologi finansial, dengan kemudahan penggunaan dan inovasi layanan keuangan digital yang meningkatkan motivasi mahasiswa untuk melakukan investasi. Lebih jauh, pemahaman yang lebih besar tentang keuntungan dan kerugian berinvestasi difasilitasi oleh tingkat literasi keuangan yangilebih tinggi, yangipada gilirannya mendorong pilihan investasiiyang lebihilogis.